Improving the quality of Cassava Peel-Leaf Mixture (CPLM) through fermentation with R. oligosphorus as poultry ration - Mirnawati; Ciptaan, Gita; Ferawati (Emirates Journal of Food and Agriculture, 2023)
Cassava (Manihot utilissima) is one of the potential food commodities in Indonesia. Cassava production in Indonesia is relatively high. Ofcourse, it will produce much waste, such as Cassava Peel (CP) and Cassava Leaf (CL). Casava peel and casava leave has the potential to be used as feed ingredients but is constrained by low quality, and they can only be used 10% in poultry rations. For that, it is necessary to research to improve the quality of Cassava Peel-Leaf Mixture (CPLM) through fermentation with R.oligosphorus as a poultry ration. This experimental study uses a completely randomized design (CRD) with four treatments and five replications. The treatments were cassava peel-leaf mixture (CPLM) fermented with R. oligosphorus. The Treatments were A (9:1), B (8:2), C (7:3), and D (6:4). The variables observed were the digestibility of crude fiber (DCF), the activity of protease enzymes, crude protein (CP) nitrogen retention (RN), metabolic energy (ME), and crude fiber (CF). The diversity analysis showed a very significant effect (P<0.01) on (DCF), crude protein (CP), protease activity, crude fiber (CF), nitrogen retention (RN), and energy metabolism (ME) of CPLM fermentation. Based on the study’s results, it can be concluded that CPLM (6:4) fermented with R.oligosphorus gave the best results. Keywords: R. oligosphorus; Casava peel; Casava leave; Fermented; Poultry